Sistem Pendukung Keputusan Penentuan Pegawai Terbaik Menggunakan Metode TOPSIS - Alexander, Jason; Dafid, Dafid (Universitas Multi Data Palembang, 2025)
The Decision Making System plays a crucial role in the intricate and dynamic landscape of modern business. The TOPSIS method is a prominent technique within this domain, utilized to generate various alternatives by evaluating multiple criteria. In the TOPSIS framework, each criterion is assigned a weight, and the ratio between each alternative and the respective criteria is calculated. These ratios are aggregated to produce a total score, facilitating the identification of the most favorable alternative. This study elucidates the fundamental principles of TOPSIS and examines its application in business decision-making processes. This method empowers decision-makers to navigate the complexities of selecting the optimal choice amid limited and often contradictory information. The benefits of TOPSIS include its capacity to simultaneously address multiple criteria and offer a structured evaluation framework. The findings of this study can yield a ranking of employees based on specified criteria such as performance, responsibility, communication, and absenteeism, utilizing the TOPSIS approach.